Faktor-faktor yang mempengaruhi gelagat kepatuhan zakat perniagaan - Ram Al Jaffri Saad,; Zainol Bidin,; Kamil Md. Idris,; Md Hairi Md Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This study attempts to gain explanation on the possible cause of low level of business zakah compliance behaviour. Using the theory of planned behaviour, this study attempts to reveal whether the basis of the theory such as attitude, subjective norm, and perceived behavioural control can explain the intention and compliance behaviour in the zakah environment. The results on 108 businessmen in Perlis shown that this research model is consistent with the theory of planned behavior. Thus, whatsoever actions or strategies that would be used shall consider the understanding of the underlying factors in the theory of planned behaviour